Prophylactic evaluation of shoulder proprioception in elite swimmers - Bernard, C.; Gillet, B.; Pizzuto, M.; Rogowski, I.; Coste, J.; Hays, A.; Barnier, R.; Sevrez, V. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
It is suggested that poor shoulder proprioception contributes to shoulder pain in swimmers. However, there is a lack of studies describing the measurement method for shoulder proprioception. The purposes of this preliminary study was to investigate the scapular position depending on arm scaption as a first step in the development of a measurement method for three-dimensional shoulder proprioception. An asymptomatic young adults participated in this study. His scapular rotation were measured as a function of arm position during scaption in two consecutive days. The results showed that scapular rotations are not a reproducible function of humerus elevation. Those findings suggested that the assessement of shoulder proprioception should rely on the evaluation of both gleno-humeral and scapulo-thoracic joints to be valid.